Hydrogenation of Benzene to Cyclohexane in Fixed Bed Reaction: Studies of Reactor Simulation - Noguchi, Yoshio; Iwamura, Takao; Otani, Seiya; Yamazaki, Toru; Akatsuka, Takeaki (Chemical engineering, 1970)
For hydrogenation of benzene accompanying high heat of reaction, temperature profiles of catalytic fixed-bed reactor were measured in a test plant. With the information obtained on the rate and physical properties of the fixed bed, it was possible to analyze the reactor performances by simulation based on a two-dimensional diff erential model. In the computations, Crank-Nicolson's fi nite difference method was employed and the results were in good agreement with experiments for various operating conditions. To obtain optimum temperature profile by diminishing the maximum temperature peak, control of the catalytic activity by mixing inactive solid with the catalyst was examined and proved effective. As the catalytic activity decayed with reaction time, a computation to show time effect on longitudinal temperature profile was made. The results indicate that the maximum temperature peak would diminish with time, while the over-all conversion is kept constant.